Directions for Improving the Efficiency of Technology Transfer Processes in the Russian Economy - Olga PYATAEVA; Liliya PRIKHODKO; Vladislav SHALAEV; Pavel SHULUS; Evgeny PAVLOV (Communications of International Proceedings, 2020)
Technology transfer is of particular strategic importance, as technology is a catalyst for the socio-economic development of economic actors at home and abroad. Technology consists of a pool of knowledge and know-how, acts as a catalyst for healthy and competitive international trade, and is linked to the commercial needs of industrial enterprises. Sectors of economy, regions and national economies in general need effective planning of research activities and management of production, from the research laboratory to the market of knowledge-based products. The tasks of creating an institutional environment for technology transfer in Russia actualize the need to develop recommendations for improving the efficiency of technology transfer, which is the subject of this article.
Keywords: Innovation; technology transfer; efficiency; technologies; Russian economy.